Cu(II) complexes of cyclotriphosphazene bearing Schiff bases: Synthesis, structural characterization, DFT calculations, absorbance and thermal properties - Dogan, Semih; Balci, Ceylan Mutlu; Senocak, Ahmet; Besli, Serap (Pergamon-Elsevier Science Ltd, 2020)
N3P3[(2,2'-biphenoxy)(2)(OC6H4N = CH-C6H4F)(2)] (L1) and N3P3[2,2'-biphenoxy(OC6H4N = CH-C6H4F)(4)] (L2), which are cyclotriphosphazene derivatives containing biphenyl-2,2'-dioxy group(s) and Schiff base moieties, were synthesized. The structures of L1 and L2 were characterized by elemental analysis, FT-IR spectroscopy, MALDI-TOF mass spectrometry, H-1 and P-31 NMR spectroscopy. Moreover, the molecular structure of L2 was unambiguously determined by X-ray crystallography. C1 and C2 were prepared from the complexation reactions of L1 and L2 with CuCl2 salts. The characterization of these complexes was carried out using various methods (elemental analysis, FT-IR spectroscopy, MALDI-TOF mass spectrometry). UV-Vis experiments, including titration and continuous variation (Job's plot analysis), proved that all of the spectrophotometric properties in the solution state support the binding mode of L-Cu2+ of the complexes C1 and C2. Theoretical DFT calculations were carried out to confirm the molecular geometry and the binding type of the Cu(II) complexes C1 and C2. The analyses revealed that the metal ion in the two novel mononuclear and dinuclear Cu(II) complexes (C1 and C2) coordinate to two imine groups of geminal Schiff bases in the eta(2) -geminal-N-2 coordination mode. The magnetic properties of C1 and C2 were analysed with VSM and ESR techniques. Furthermore, the thermal properties of L1, L2, C1 and C2 were investigated and the results were compared and discussed. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Copper complexes; Schiff bases; Cyclophosphazenes; UV-Vis absorption; Thermal analysis